Potential Significance of Peptidome in Human Ovarian Cancer for Patients With Ascites. Issue 2 (February 2018) - Huang, Xiaohao; Zhou, Juan; Tang, Ranran; Han, Suping; Zhou, Xue
Abstract : Objective: Ovarian cancer (OC) is one of the lethal gynecological malignancies. Most women affected by OC with malignant ascites will relapse. Peptidomics, as an emerging branch of proteomics, is more applied in screening of disease biomarkers, diagnosis, treatment, and monitoring. However, there is still little in-depth analysis about peptidomics study in OC with malignant ascites. Methods: A comparative peptidomic profiling of ascites fluid between 6 OC patients and 6 benign gynecological conditions using liquid chromatography-tandem mass spectrometry was analyzed. Afterward, the Ingenuity Pathway Analysis was performed to reveal the potential function of peptide-protein precursors. Results: A total of 4388 nonredundant peptides were identified, 104 of which were significantly differentially expressed in the ascites fluid of OC and benign gynecological conditions (>2-fold changes and P < 0.05): 52 peptides were upregulated while 52 peptides were downregulated. These peptides were imported into the Ingenuity Pathway Analysis and identified putative roles in OC. Conclusions: We identified the peptidome patterns of patients with OC and benign gynecological conditions, and these differentially expressed that peptides might play an important role during occurrence and development of OC and will be in hope to explore bioactive peptides in the pathogenesis of OC.